Pengaruh Sistem Informasi Akuntansi, Literasi Keuangan, Dan Akses Permodalan Terhadap Kinerja Usaha Mikro Kecil Dan Menengah (UMKM) Se-kecamatan Kediri - Witari, Ni Made Ari; Erlina Wati, Ni Wayan Alit; Padnyawati, Kadek Dewi (Hita Akuntansi dan Keuangan, 2025)
The performance of Micro, Small and Medium Enterprises is one of the benchmarks for achieving business goals. Improving performance is the key for a business to develop and compete successfully and prevent bankruptcy. This research aims to examine the influence of accounting information systems, financial literacy and access to capital on the performance of MSMEs. This research used a quantitative approach by determining the sample using the Slovin formula with an error rate of 10%, which resulted in a total of 100 respondents in MSMEs in Kediri District. The sample was selected using the Simple Random Sampling method, and data was collected through a questionnaire. The data used is primary data in the form of responses from respondents, and processed using SPSS. The results of this research show that accounting information systems (X1), financial literacy (X2), and access to capital (X3) have a positive and significant effect on the performance of MSMEs (Y) in Kediri District. The better the accounting information system, financial literacy and access to capital, the better the performance of MSMEs in Kediri District.